The Effects of Feedback on The Ability to Mathematic Problem Solving on Linear Inequality of One Variable for Ninth Grade Students: Application of Frey and Fisher Model - Saengsawang, Duangkamol; Masantiah, Chuthaphon; Tippayakulpairoj, Darunee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Mathematical problem-solving is an important skill in learning management in mathematics. Teachers should train students to develop their ability to solve mathematical problems regularly. As well as allowing students to solve math problems by themselves to know the shortcomings that need improvement. Including providing feedback and reflection on learning outcomes to students. Consequently, the purpose of this research was to compare students’ mathematical problem-solving abilities before and after receiving feedback using Frey and Fisher’s model. Methodology: The research sample group was the grade 9 students from Chitjaichuen school in the first semester of the academic year 2023, a total of 29 students from cluster random sampling. The research instrument used consisted of (1)3 Frey and Fisher’s model learning management plans, which each learning management plan has the highest level of appropriateness (2) 3 Problem-solving work sheets with reliability values of 0.791, 0.903, and 0.864, respectively. Difficulty values were in the range of 0.240 - 0.604 and discriminatory power values were in the range of 0.438 - 0.750 and (3) Problem-solving ability test on the Linear Inequality of One Variable. There were 2 versions with reliability values of 0.916, and 0.788, respectively. Difficulty values were in the range of 0.366 – 0.625 and discriminatory power values were in the range of 0.411 – 0.833. The data analysis statistics were frequency, percentage, mean, standard deviation, and dependent sample t-test. Results: The mathematical problem-solving ability of students by providing feedback using Frey and Fisher’s model after learning was significantly higher than before learning at the .05 level. (t = 13.877, p = .000) Conclusion: Results indicated that students’ mathematical problem-solving skills showed significant and statistically significant improvements. When they received feedback using Frey and Fisher’s model after engaging in learning activities. It is seen that this improvement is not likely due to chance. It provides clear evidence of the effectiveness of feedback approaches in increasing mathematical problem-solving abilities.